Managing airports : an international perspective - Graham, Anne, 1958- (New York, NY : Routledge, 2023)
"Fully revised and updated to consider recent developments in the industry, the sixth edition of Managing Airports: An International Perspective provides comprehensive and cutting-edge insight into the processes behind running a successful airport. International and multi-disciplinary in approach, this edition is a vital resource for students, lecturers and researchers of transport and tourism, and practitioners within the air transport industry"--
Revised edition of the author's Managing airports, 2018.
OCLC-licensed vendor bibliographic record.
Keywords: Airports -- Management; TRANSPORTATION / Aviation / General; TRAVEL / General